Eye location and eye state detection in facial images using circular Hough transform - Söylemez, Ömer Faruk; Ergen, Burhan (My University, 2013)
Recently, eye states are used as inputs to various applications such as facial expression recognition systems, human-computer interaction and driver fatigue detection systems. Especially with the prominence of human computer interaction, eye state detection has drawn great attention in the past decade. In this study, an eye state detection system based on Circular Hough Transform (CHT) has been offered. Initially, face and eye images are extracted from given gray-level images. After some preprocessing steps, existence of circular iris structure is searched within the extracted eye image using CHT. Existence of circular iris structure is searched within the eye image with the help of circular Hough transform. Eyes are decided as open if iris could identified as a circle. © 2013 IFIP International Federation for Information Processing.
12th IFIP TC8 International Conference on Computer Information Systems and Industrial Management, CISIM 2013 -- 25 September 2013 through 27 September 2013 -- Krakow -- 99900
Keywords: Circular Hough transform; Eye state detection